Healthy mothers, happy children. Prenatal assessment for psychosocial factors in public hospitals of the Republic of Cyprus - Hadjigeorgiou, Eleni; Koliandri, Yianna; Spyridou, Andria (My University, 2020)
Background: Maternal mental health has received an increased research interest as it has direct impact on the mother's psychosocial wellbeing and the fetus/child's health and development. Many psychosocial risks factors have found to interplay a crucial role for pregnancy, maternal and neonatal outcomes. the aim of this study was to explore the psychosocial risk factors that may affect pregnant women and examine the feasibility of the KiNDeX Mum-screen for the early detection of women at risk, in the daily practice of health professionals providing prenatal care in public health settings in Cyprus. MethODs: Mixed-methods design was carried out using the adapted Greek version of KiNDeX questionnaire and reflective diaries by the midwives that conducted the interviews. Three hundred one pregnant women were interviewed in five public hospitals of Cyprus by 14 midwives. Upon conclusion of the interviews, the midwives wrote reflective diaries, and thematic analysis was conducted. RESULTS: The results of the quantitative analysis suggest that the KINDEX sum score was significantly higher for participants reporting a risk factor from the eleven risk areas. The PSS-4 was higher for those participants with financial related concerns in the future and for participants that experienced life-long intimate partner violence. From the analysis of the qualitative data, three main themes emerged: 1) health professionals should have the ability to identify psychosocial factors that affect pregnant women and babies' health in their everyday practice; 2) feasibility of the interview in public health care settings; 3) partnership between women and health professionals. cONcLUsiONs: in Cyprus, where the cesarean rates are reaching 60%, one of the highest worldwide, there are a huge space for improvement in the perinatal care provided. health professionals should have the opportunity to use screening tools and provide evidence based, cost effective, and human rights oriented mental health and social care services. Policy makers should create strategies for promotion of psychosocial well-being of mothers during pregnancy aiming at maximizing the neonatal and perinatal outcomes, including the indirect outcomes, such as mother-child bond and child development. the KiNDeX mum-screen was a well-accepted and user-friendly tool by the midwives, within a challenging public health setting. concluding this study and based on the outcomes we consider that this is a valid prenatal screening tool for identification of psychosocial risk factors.
Keywords: Cyprus; Mental health; Nurse midwives; Pregnant women